Uptake of prevention of mother-to-child-transmission using Option B+ in northern rural Malawi: a retrospective cohort study - Price, Alison J (BMJ Publishing Group, 2014)
To identify points of dropout on the pathway from offering HIV testing to maintenance on antiretroviral therapy (ART), following the introduction of the Option B+ policy for pregnant women in Malawi (lifelong ART for HIV-positive mothers and 6 weeks nevirapine for the infants), a retrospective cohort study within a demographic surveillance system in northern Malawi. Women living in the demographic surveillance system who initiated antenatal care (ANC) between July 2011 (date of policy change) and January 2013, were eligible for inclusion. Women who consented were interviewed at home about their health facility attendance and care since pregnancy, including antenatal clinic (ANC) visits, delivery and postpartum care. Women's reports, patient-held health records and clinic health records were manually linked to ascertain service use. Among 395 women, 86% had tested for HIV before the pregnancy, 90% tested or re-tested at the ANC visit, and <1% had never tested. Among 53 mothers known to be HIV-positive before attending ANC, 15 (28%) were already on ART prior to pregnancy. Ten women tested HIV-positive for the first time during pregnancy. Of the 47 HIV-positive mothers not already on ART, 26/47 (55%) started treatment during pregnancy. All but five women who started ART were still on treatment at the time of study interview. HIV testing was almost universal and most women who initiated ART were retained in care. However, nearly half of eligible pregnant women not on ART at the start of ANC had not taken up the invitation to initiate (lifelong) ART by the time of delivery, leaving their infants potentially HIV-exposed.